Study rationale, design, and pretransplantation alloantibody status: A first report of Clinical Trials in Organ Transplantation in Children‐04 (CTOTC‐04) in pediatric heart transplantation. Issue 9 (23rd March 2018) - Zuckerman, Warren A.; Zeevi, Adriana; Mason, Kristen L.; Feingold, Brian; Bentlejewski, Carol; Addonizio, Linda J.; Blume, Elizabeth D.; Canter, Charles E.; Dipchand, Anne I.; Hsu, Daphne T.; Shaddy, Robert E.; Mahle, William T.; et al.
Abstract : Anti‐HLA donor‐specific antibodies are associated with worse outcomes after organ transplantation. Among sensitized pediatric heart candidates, requirement for negative donor‐specific cytotoxicity crossmatch increases wait times and mortality. However, transplantation with positive crossmatch may increase posttransplantation morbidity and mortality. We address this clinical challenge in a prospective, multicenter, observational cohort study of children listed for heart transplantation (Clinical Trials in Organ Transplantation in Children‐04 [CTOTC‐04]). Outcomes were compared among sensitized recipients who underwent transplantation with positive crossmatch, nonsensitized recipients, and sensitized recipients without positive crossmatch. Positive crossmatch recipients received antibody removal and augmented immunosuppression, while other recipients received standard immunosuppression with corticosteroid avoidance. This first CTOTC‐04 report summarizes study rationale and design and relates pretransplantation sensitization status using solid‐phase technology. Risk factors for sensitization were explored. Of 317 screened patients, 290 were enrolled and 240 underwent transplantation. Core laboratory evaluation demonstrated that more than half of patients were anti‐HLA sensitized. Greater than 80% of sensitized patients had class I (with or without class II) HLA antibodies, and one‐third of sensitized patients had at least 1 HLA antibody with median fluorescence intensity of ≥8000. Logistic regression models demonstrated male sex, weight, congenital heart disease history, prior allograft, and ventricular assist device are independent risk factors for sensitization. Abstract : This first report from the cardiac consortium of the NIAID/NIH‐sponsored CTOTC summarizes study rationale and design, and uses a large multi‐institutional cohort to establish the incidence and risk factors for presensitization prior to pediatric heart transplantation. See the related papers onpages 2148 and2163, and the editorial from Pajaro et al onpage 2107 .